Effect of biomedical complications on very and extremely preterm children's language - Varela-Moraga, Virginia; Diethelm-Varela, Benjamín; Pérez-Pereira, Miguel (Frontiers in Psychology, 2023)
Introduction Very and extremely preterm children have been found to show delays in the development of language in early years. In some investigations, however, a rigorous control of biomedical complications, such as Periventricular Leukomalacia (PVL), Intraventricular Hemorrhage (IVH) or Bronchopulmonary Dysplasia (BPD), does not always exist. For that reason, a confounding effect of low gestational age and biomedical complications may lead to erroneous conclusions about the effect of gestational age. Methods In this investigation we compare language development [use of words, sentence complexity and mean length of the three longest utterances (MLU3)] of three groups of Chilean children at 24 months of age (corrected age for preterm children). The first group was composed of 42 healthy full-term children (Full term group: FT), the second group of 60 preterm children born below 32 gestational weeks without medical complications (low risk preterm group: LRPT), and the third group was composed of 64 children below 32 gestational weeks who had medical complications (High risk preterm group: HRPT). The three groups were similar in terms of gender distribution, maternal education, and socio-economic environment. The instrument used to assess language was the Communicative Development Inventories (CDI). In addition, the Ages and Stages Questionnaire-3 (ASQ-3) was also used to assess other developmental dimensions. Results The results indicate that HRPT and LRPT children obtained significantly lower results than the FT group in the three language measures obtained through the CDI. No significant differences were observed between the HRPT and the LRPT groups, although the HRPT obtained the lowest results in the three CDI measures. The results obtained through the administration of the ASQ-3 confirm the delay of both preterm groups in communicative development when compared to the FT group. No significant differences between the FT and the PT groups were observed in gross motor, fine motor and problem solving dimensions of the ASQ-3. The LRPT group obtained results that were significantly higher than those of the FT group and the HRPT group in gross motor development. Discussion These results seem to indicate that the area of language development is particularly influenced by very or extremely low gestational age.